Pengaruh Iklan di Televisi dan Kualitas Produk Terhadap Motivasi Pembelian Pelanggan Shampo Sunsilk pada Mahasiswi di STIE Sakti Alam Kerinci - Gampo Haryono (Universitas Batanghari Jambi, 2018)
This study aims to analyze the ads on television and product quality to the Motivation Purchase customers sunsilk shampoo on students at STIE Sakti Alam Kerinci. This type of research is causative research. Sampling research Using purposive sampling technique by distributing questionnaires to 50 respondents. The data analysis used is multiple linear regression. The results showed that: (1) The influence of advertisement on television has no effect on purchasing motivation, It is proved by, t value < t table (1,573 < 2.012) and significance > 0,05 (0,122> 0,05) received and Ha rejected, meaning there is no significant influence between Advertising on Television Against Motivation Purchase Customer Sunsilk Shampoo on students in STIE Sakti Alam Kerinci. (2) Product Quality significantly influence Purchase Motivation, This is proved by, the value of t calculate > t table (2,669> 2,012) and significance <0,05 (0,010 <0,05), hence Ho is rejected and Ha is received, it means partially there is significant influence between Quality of Product to Motivation Purchase Customer Sunsilk Shampoo on students at STIE Sakti Alam Kerinci. Keyword : Ads on Television, Product Quality and Motivation Purchase